2023
DOI: 10.3390/ani13152419
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Visual-Only and Visual-Palpation Post-Mortem Lung Scoring Systems in Slaughtering Pigs

Abstract: Respiratory diseases continue to pose significant challenges in pig production, and the assessment of lung lesions at the abattoir can provide valuable data for epidemiological investigations and disease surveillance. The evaluation of lung lesions at slaughter is a relatively simple, fast, and straightforward process but variations arising from different abattoirs, observers, and scoring methods can introduce uncertainty; moreover, the presence of multiple scoring systems complicates the comparisons of differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Although lung scoring activities at slaughter are generally considered a relatively simple and rapid process, some important limitations may emerge, related to potential biases and feasibility. The selection of the most suitable scoring system is essential to collect high-quality data, and it must take into account the objectives of the assessment and its final use [ 39 ]. The reliability of the collected information depends on the reproducibility and objectivity of the selected method; therefore, scoring systems involving a certain degree of subjectivity should be avoided [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although lung scoring activities at slaughter are generally considered a relatively simple and rapid process, some important limitations may emerge, related to potential biases and feasibility. The selection of the most suitable scoring system is essential to collect high-quality data, and it must take into account the objectives of the assessment and its final use [ 39 ]. The reliability of the collected information depends on the reproducibility and objectivity of the selected method; therefore, scoring systems involving a certain degree of subjectivity should be avoided [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…The implementation of commonly recognized and validated guidelines at a national and European level would allow for the collection of comparable and harmonized data across different countries, reducing the variability and ensuring consistency in the assessment process. To achieve this, a comprehensive training program for veterinarians is of paramount importance [ 39 ]. In addition, regular training and calibration sessions may be useful to ensure that assessors continue to score lung lesions properly over time.…”
Section: Discussionmentioning
confidence: 99%
“…Herein, we showed that the same CNN provides good results even when compared with the best scenario, i.e., scores given by a skilled operator after careful inspection and palpation. Interestingly, Ghidini et al [18] have shown that visual-only methods (namely Blaha's scoring system) can be suitable, although they are less sensitive in scoring pneumonia in slaughtered pigs. Blaha's and Madec's methods demonstrated a strong and significant correlation (Spearman's coefficient of 0.81, p < 0.001), their agreement being particularly good for medium-to-large-sized lesions [18].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, Ghidini et al [18] have shown that visual-only methods (namely Blaha's scoring system) can be suitable, although they are less sensitive in scoring pneumonia in slaughtered pigs. Blaha's and Madec's methods demonstrated a strong and significant correlation (Spearman's coefficient of 0.81, p < 0.001), their agreement being particularly good for medium-to-large-sized lesions [18]. Overall, such data match those reported in this study.…”
Section: Discussionmentioning
confidence: 99%